(untitled) (The Journal of Psychology and Sociology, 2013)
This article describes the dynamic model of a sense of sympathetic joy primary school children which is based on the results of the experimental work of the authors. The detailed description of one of the working methods, “If I was a wizard ...” and analysis. Studies V.V. Abramenkova showed that the sense of sympathetic joy of children under 7 years is complete. In our study, we saw the collapse of a sense of sympathetic joy in the real and the imaginary.Under a real sense of sympathetic joy, we mean little controlled verbal and nonverbal behavior. Under an imaginary sense of sympathetic joy means controlled behavior, such as writing, where primary school children asked to describe their behavior in an imaginary situation.